APPLICATION OF INDEPENDENT LEARNING TO LEARN MATHEMATICS BASED ON PROBLEMS HOTS SANTRI 7TH GRADE MTS PESANTREN AL KHAIRAAT AMBON THROUGH PBL - Nani Sukartini Sangkala; Patma Sopamena; Syafruddin Kaliky; Muhammad Qashai Ramdani Pelupessy; Fahruh Juhaevah (IAIN Ambon, 2022)
This study aims to determine the influence of the application of independent learning in HOTS-based mathematics learning on students of 7th grade, MTs Pesantren Al Khairaat Ambon through PBL. This study used a descriptive quantitative approach with a population sample, and all 7th-grade MTs Pesantren Al Kahiraat Ambon students totaled 12 people in 1 study group. Research instruments are: Test questions (pre-test and post-test) are used to measure student learning outcomes before and after learning with PBL, and questionnaires are used to measure student responses after implementing PBL. The test questions completed by students are in the form of HOTS, which contains problems in students' daily lives that are solved by requiring problem-solving analysis. The results showed an influence on the application of independent learning in mathematics based on HOTS on the learning outcomes of 7th grade MTs students of Pesantren Al Khairaat Ambon through PBL. The effect of the application of learning is characterized by a significant difference between the pre-test and the post-test of 7th grade MTs students of Pesantren Al Khairaat Ambon. Based on the Wilcoxon sign rank test obtained a significance value of 0.004 < 0.05, then the null hypothesis (Ho) was rejected, and accepted the alternative hypothesis (Ha). That is, there is a significant difference between the results of learning pre-test and post-test (with the average condition of the post-test value being more than the Pre Test). The aspect of independent learning in this study has not been strictly observed. Therefore further research needs to be given strict attention.Keywords: Independent Learning Mathematics; HOTS Problems; Problem-Based Learning.